Chondrule sizes within the CM carbonaceous chondrites and measurement methodologies - Floyd, CJ; Benito, S; Martin, P; Jenkins, LE; Dunham, E; Daly, L; Lee, MR (Wiley, 2024)
The sizes of chondrules are a valuable tool for understanding relationships between meteorite groups and the affinity of ungrouped chondrites, documenting temporal/spatial variability in the solar nebula, and exploring the effects of parent body processing. Many of the recently reported sizes of chondrules within the CM carbonaceous chondrites differ significantly from the established literature average and are more closely comparable to those of chondrules within CO chondrites. Here, we report an updated analysis of chondrule dimensions within the CM group based on data from 1937 chondrules, obtained across a suite of CM lithologies ranging from petrologic subtypes CM2.2 to CM2.7. Our revised average CM chondrule size is 194 μm. Among the samples examined, a relationship was observed between petrologic subtype and chondrule size such that chondrule long‐axis lengths are greater in the more highly aqueously altered lithologies. These findings suggest a greater similarity between the CM and CO chondrites than previously thought and support arguments for a genetic link between the two groups (i.e., the CM‐CO clan). Using the 2‐D and 3‐D data gathered, we also apply numerous stereological corrections to examine their usefulness in correcting 2‐D chondrule measurements within the CM chondrites. Alongside this analysis, we present the details of a standardized methodology for 2‐D chondrule size measurement to facilitate more reliable inter‐study comparisons.